Mathematical methods in chemical engineering - Arvind Varma (Oxford University Press, 1997)
Mathematical Methods in Chemical Engineering builds on students' knowledge of calculus, linear algebra, and differential equations, employing appropriate examples and applications from chemical engineering to illustrate the techniques. It provides an integrated treatment of linear operator theory from determinants through partial differential equations, featuring an extensive chapter on nonlinear ordinary differential equations as well as strong coverage of first-order partial differential equations and perturbation methods. The text offers instructors the flexibility to cover all of the material presented or to select a few methods to teach, so that they may cultivate the specific mathematical skills which are most appropriate for their students. The topical coverage provides a good balance between material which can be taught in a one-year course and the techniques that chemical engineers need to know to effectively model, analyze, and carry out numerical simulations of chemical engineering processes, with an emphasis on developing techniques which can be used in applications